Effects of E-commerce on Local Labor Markets - Anahid Bauer; Sofía Fernández Guerrico (Institute of Labor Economics (IZA), 2023)
This paper studies the effect of e-commerce on local labor markets. We exploit cross-market variation in e-commerce price advantage stemming from the enactment of the Amazon Tax-state-level legislation that mandates state sales taxes collection to out-of-state online retailers. Introducing out-of-state sales taxes lowered employment and reduced wages in transportation and warehousing, industries complementary to e-commerce. Within the in-state retail sector, the decline in brick-and-mortar employment is somewhat offset by an increase in employment in warehouse clubs and supercenters. Our results are consistent with a general equilibrium model in which consumers substitute e-commerce for big-box purchases, crowding out brick-and-mortar retail.
Keywords: H71; J2; L81; O33; 330; e-commerce; retail; employment; Amazon Tax